Pest Arthropods with Holocentric Chromosomes are More Resistant to Sterilizing Ionizing Radiation - Zedek, František; Bureš, Petr (Radiation research, 2019)
It has been hypothesized that species with holocentric chromosomes have a selective evolutionary advantage for developmental and reproductive success because holocentric chromosomes are less susceptible to chromosome breakage than monocentric chromosomes. We analyzed data on sterilizing doses of ionizing radiation for more than 250 species of arthropods to test whether the minimal dose for reproductive sterilization is higher for species with holocentric chromosomes than for species with monocentric chromosomes. Using linear mixed models that account for phylogeny, we show that holocentric arthropods are more tolerant of sterilizing radiation than monocentrics. Moreover, higher dose rates correlate with lower sterilizing doses in monocentrics, but not in holocentrics, which is a novel finding that may be of importance for radiosanitation practice. Under the dose rate of 1 Gy/min, holocentric arthropods are sterilized on average with a 2.9 times higher minimal dose than monocentrics. Life stage and sex have significant but considerably weaker effects on sterilizing dose than chromosome type. Adults and males require 1.2 and 1.4 times higher sterilizing doses than juveniles and females, respectively. These results support the hypothesis that holocentric lineages may originate and thrive better in times of increased exposure to chromosome-breaking factors.
Keywords: Chromosomes; mužské pohlaví; ženské pohlaví; Pest Control; zvířata; kontrola škůdců; Arthropods; Sterilization; Female; sterilizace; Male; Chromosome Breakage; členovci; chromozomy; zlomy chromozomů; Animals